Pembelajaran Mata Pelajaran Al-Islam Di SD Muhammadiyah Mrisi Kabupaten Bantul - Lukman Nur Huda; Siti Aisyah (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2018)
This evaluation study discusses the implementation of education of Al-Islam subject learning at Muhammadiyah Elementary School Mrisi, Bantul district. Supporting factors and inhibitors also become an integral part of study. The results of this qualitative study suggest developing Al-Islam subject learning in the classroom. Nevertheless the learning of other Islamic religious education (PAI) outside the classroom can have an impact on the success of learning Al-Islam compared to discourage it. Such research is expected to have beneficial for the development of PAI learning in Muhammadiyah Elementary School that brings about change in achieving overall educational progress.